INTERNATIONAL EXPANSION THROUGH START-UP OR ACQUISITION: A LEARNING PERSPECTIVE. - Barkema, H. G.; Vermeulen, F. (Academy of Management Journal, 1998)
This study brings a fresh approach—a learning perspective—to the literature examin-ing whether firms expand internationally through start-ups or acquisitions. Hypothe-ses concern how this strategic choice is influenced hy a firm's multinational diversity and product diversity. The results show that multinational diversity leads to foreign start-ups rather than acquisitions. Product diversity has a curvilinear efiect on the tendency to use start-ups. The curvilinear effect becomes weaker at higher levels of multinational diversity. Firms can internationalize in a number of ways, including through exports, licensing, and foreign direct investments (e.g.. Dunning, 1980,1988). For-eign direct investments (FDIs) have increased dra-matically over the last few decades, both in relative and absolute terms, reaching annual growth rates of nearly 30 percent and a worldwide total of about $1.5 trillion in the late 1980s (United Nations,